Delta Opioid Peptide [d-Ala2, d-Leu5] Enkephalin (DADLE) Exerts a Cytoprotective Effect in Astrocytes Exposed to Oxygen-Glucose Deprivation by Inducing Autophagy. Issue 6 (June 2019) - Wang, Shuyan; Cao, Xiaoqiong; Duan, Yale; Zhang, Guangming
Astrocytes protection and functional regulation are important strategies to protect against neuronal damage caused by ischemia. Activation of the delta opioid receptor (DOR) could reduce astrocytes damage, although the mechanism remains unclear. The present study aimed to test the effect of DOR activation on autophagy in astrocytes exposed to oxygen-glucose deprivation (OGD), and to further investigate whether this effect has a protective effect on astrocytes. Primary cultured rat cortical astrocytes were treated with various doses of [d -Ala2, d -Leu5]-Enkephalin (DADLE, a selective DOR agonist) followed by 6 h OGD. Cell viability was evaluated by CCK-8 assay and lactate dehydrogenase release. Autophagic vacuole was analyzed with LC3 immunofluorescent staining. The levels of autophagy and apoptosis-related proteins were analyzed by western blot. Results demonstrated that treatment with 10 nM DADLE was sufficient to increase cell viability and induced autophagy in astrocytes. The DADLE-induced autophagy displayed a cytoprotective effect on astrocytes. Inhibition of autophagy by 3-methyladenine (3-MA, an autophagy inhibitor) reversed the protective effect of DADLE. Naltrindole (a DOR antagonist) only partially antagonized the role of DADLE, which indicated that DADLE might have a cytoprotective mechanism independent of DOR. Further results showed that DADLE significantly enhanced the level of Bcl-2 protein and reduced the level of Bax protein in astrocytes exposed to OGD. Our results suggest a novel mechanism in which DADLE induces autophagy in astrocytes and exerts cytoprotective effects by inhibiting apoptosis.